1970
DOI: 10.1525/aa.1970.72.1.02a00060
|View full text |Cite
|
Sign up to set email alerts
|

The Personal Adjustment of Navajo Indian Migrants to Denver, Colorado1

Abstract: Urban migration creates many adjustment problems for those American INTRODUCTIONN E WEDNESDAY morning in mid-0 September a young Indian stepped off the bus at the Trailways depot in downtown Denver, Colorado. Like most Navajo migrants, Harrison Joe2 was in his early twenties and single. He had graduated two years before from the Special Navajo Program at Intermountain School in Brigham City, Utah. This program, now discontinued, was a five-year course for Navajos with little or no prior educational experience.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1975
1975
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The literature also notes that older American Indians are less successful at adjustment and more likely to return to their reservations (Ablon 1964;Graves 1970;Graves and Van Arsdale 1966;Guillemin 1975;Price 1968). The concept "older" was not generally defined, and readers might mistakenly infer postretirement age.…”
Section: Demographicsmentioning
confidence: 99%
“…The literature also notes that older American Indians are less successful at adjustment and more likely to return to their reservations (Ablon 1964;Graves 1970;Graves and Van Arsdale 1966;Guillemin 1975;Price 1968). The concept "older" was not generally defined, and readers might mistakenly infer postretirement age.…”
Section: Demographicsmentioning
confidence: 99%
“…About 35 per cent returned to the reservation within a short period. In his more recent study of Navajo relocatees in Denver, Graves (1970) found that about two-thirds returned to the reservation within a ten-year period.…”
Section: Navajo Populationmentioning
confidence: 98%
“…The weakness of his logic is nicely exemplified by Graves and Graves (1970), who discovered that the most achievement oriented Native migrants to the city were most likely to experience frustration and return home. Workman (1996) documents the widespread acceptance, in Atlantic Canada, of government claims of impotency in underwriting social programs.…”
Section: Notesmentioning
confidence: 99%
“…Note McClelland's work (1966) on the "need for achievement" training, which does not mention whether opportunities will be available for those whose ambitions have been artificially raised. The weakness of his logic is nicely exemplified by Graves and Graves (1970), who discovered that the most achievement oriented Native migrants to the city were most likely to experience frustration and return home. Unfortunately, the fallacy persists and underwrites policy (in "supply-side" economics).…”
Section: Notesmentioning
confidence: 99%